PENGGUNAAN METODE KARTU UNTUK MENINGKATKAN PEMAHAMAN KATA SIFAT SISWA KELAS 2 SMP KEMALA BHAYANGKARI - Rabitha, Dian Septi; Ina, Ina; Suhardi, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractIn vocabulary teaching, adjective is one of the most important types of words. Most of the sentences have adjective. But many students have trouble is learning adjectives. They think the adjectives are difficult to learn and hard to remember. Second grade junior high school of Kemala Bhayangkari students have the same thinking as well. The writer used card method is teaching Kemala Bhayangkari junior high school students in teaching adjective. In order to help student get maximum result, the writer did a research. Writer gave students a test to Kemala Bhayangkari junior high school sudents to know their first condition, after that using card method to get maximum result in three times meeting. After teaching using this method, writer gave a final test to the students. At the time of pretest the result show 45 , after doing research using the card method the increased to 75 . The comparison result shows, learning outcomes using the card method improved significantly, and teaching using the card method got very well respons from student. Â Keywords:Â Adjectives, Card Method Teaching, Test